PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM BINA MARGA KABUPATEN MUSI RAWAS - Muhammad Effendi (Jurnal Interprof, 2021)
The problem in this study is the lack of organizational culture and motivation for the performance of employees at the Public Works Office of Bina Marga, Musi Rawas Regency, so that employee performance is less than optimal and not in accordance with expectations. This research is a quantitative study that uses data collection methods by observing and recording directly at the research site (observation), conducting direct questions and answers at the source using a questionnaire (questionnaire), and documentation by reading literature guidelines. The results showed that organizational culture and motivation greatly influenced the performance of employees at the Public Works Office of Bina Marga, Musi Rawas Regency. It can be concluded that a good organizational culture and high motivation can produce performance in accordance with the expectations of the organization or leader.